Efeitos da modulação da velocidade de Fermi e de localização em nanoﬁtas de grafeno - SANTOS JUNIOR, Marconi Silva (2020)
The semiconductor industry is approaching the limit of performance for current silicon dominated technologies. An alternative to these devices are graphene based devices. Graphene is composed of a single atomic layer of graphite and its peculiar electronic properties indicate the possibility of overcoming current technologies limitations. One of the most important eﬀects on electronic transport is the localization eﬀect, known as Anderson’s localization. However, there is an increased interest in the anomalous localization eﬀect. Graphene can be classiﬁed according to the type of edge: armchair and zigzag edges. In this work, we investigated the eﬀect of localiting electronic waves through a two-dimensional graphene ribbon with armchair and zigzag edges. In the ﬁrst part of the study, we consider two regions A and B with the same width and with diﬀerent velocities Fermi, vA 6= vB. For the graphene nanoribbon with Armchair edges, each region has ten atoms. For Zigzag edges, each region has eight atoms. These regions were distributed according to the Fibonacci sequence. In the second part, we analyze the transmission through N regions A and B (ABAB • • • ). Next, we analyzed the Fano factor for these same nanoribbons. We were able to observe that if the system has interaction between second neighbors, a gap appears between the conduction and valence bands, as a result, a step in conductance. When we calculate the transmission for a sequence of AB regions, the system localizes exponentially, which is not the case for zigzag nanoribbon. In the fano factor for armchair edges, all curves from the ﬁrst six generations of the Fibonacci sequence start from the same point for E/tA = 0, this eﬀect does not appear in the nanoribbon with zigzag edges.